Epidemic of life becoming a contagious Christian to reach a desperate world - Thackery, Chris (Milton Keynes, England Word Pub., 2000)
How can we over flow with life in the way that Jesus did? its time to think in a new dimension to discover how we can become an epidemic of life to our nation. The author offers a hands-on approach to some of the big challenges that face the church today
Keywords: Christian life; Christian Mission & evangelism; Christian religious experience